Sexual selection and sperm diversity in primates. (1st December 2020) - Martinez, Guillaume; Garcia, Cécile
Abstract: Many aspects of primate sperm physiology and reproductive behavior have been influenced by sexual selection, especially in taxa exposed to sperm competition where females mate with multiple partners. Primate sperm diversity reflects therefore the evolutionary divergences of the different primate species and the impact of a combination of variables exerting selection pressures on sperm form, function, and competition. Thereby, mating systems, life cycle or ecological variables are some of the important factors driving sperm diversity and explaining variation in terms of sperm morphology, parameters or male sexual characters. Here, we address primate sperm diversity through a compilation of all data available in the literature concerning primate sperm parameters and relationships between them. We also review the factors that can influence primate sperm diversity (e.g. mating systems, trade-off between investments in precopulatory and postcopulatory sexual traits, male and female sexual behaviors, seasonality, social constraints, testosterone levels), and discuss also their relevance to our understanding of human reproduction. Highlights: There is a great diversity in the andrology and sperm parameters of primates. Sperm features were described for only a small part of the known primate species. We compiled all data available on primate sperm morphology and parameters. We shed light on the factors and mechanisms driving sperm diversity across primates.